2014
DOI: 10.1159/000369967
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Septic Shock due to Spontaneous Esophageal Perforation 96 Hours after Onset by Drainage and Enteral Nutrition

Abstract: Spontaneous esophageal perforation is relatively uncommon, but carries a high mortality rate if diagnosis or treatment is delayed. We report the case of a 68-year-old man with spontaneous esophageal perforation who was successfully treated over 96 h after onset by thoracic drainage and jejunostomy for enteral nutrition. He vomited after drinking alcohol, soon followed by epigastralgia. Heart failure was suspected on admission to another hospital. Spontaneous esophageal perforation was diagnosed 48 h after admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The result of this research indicates that the use of enteral nutrition during conventional treatment of elderly patients with heart failure helps to maintain patients’ gastrointestinal function, promote protein synthesis, improve patients’ nutrition status, adjust inflammatory cytokine levels, and improve cardiac function. 12 14 The longer the treatment period is, the more obvious the improvement in cardiac function and inflammatory cytokine levels will be. Patients on free diet showed no obvious improvement in nutrition indicators after the treatment, the levels of some indicators having even decreased.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this research indicates that the use of enteral nutrition during conventional treatment of elderly patients with heart failure helps to maintain patients’ gastrointestinal function, promote protein synthesis, improve patients’ nutrition status, adjust inflammatory cytokine levels, and improve cardiac function. 12 14 The longer the treatment period is, the more obvious the improvement in cardiac function and inflammatory cytokine levels will be. Patients on free diet showed no obvious improvement in nutrition indicators after the treatment, the levels of some indicators having even decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies recommend gastric decompression to reduce persistent contamination ( 1 , 3 ). Early enteral nutrition and aggressive debridement and drainage of any infected or nonviable tissue and fluid are critical in the management of esophageal perforations ( 11 , 25 ). In the current study, all patients underwent gastric decompression with either a nasogastric or gastrostomy tube placement due to the increased risk of delayed gastric emptying in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have noted unusual symptoms such as epigastric pain or interscapular back pain that progressed to chest pain and dysphagia. 8 They suggested that chest pain after sustained strain may be indicative of esophageal perforation. 9,10 Although barium esophagography has up to 10% false-negative results, it is the standard method for diagnosis of esophageal perforation.…”
Section: Discussionmentioning
confidence: 99%